Predictors of young people's healthcare access in the digital age. (2nd October 2019) - Robards, Fiona; Kang, Melissa; Luscombe, Georgina; Sanci, Lena; Steinbeck, Katharine; Jan, Stephen; Hawke, Catherine; Kong, Marlene; Usherwood, Tim
Abstract: Objective : To quantify barriers to healthcare for young people (12–24 years) and identify socio‐demographic correlates and predictors. Methods : This cross‐sectional survey targeted young people living in New South Wales, Australia, with oversampling of marginalised groups. Principles Component Analysis (PCA) identified clusters of barriers. Ordinal regression identified predictors of each barrier cluster. Results : A total of 1, 416 young people completed surveys. Participants with chronic conditions and increasing psychological distress reported a greater number of barriers. Of 11 potential barriers to visiting a health service, cost was most common (45.8%). The PCA identified three clusters: structural barriers (61.3%), attitudinal barriers (44.1%) and barriers relating to emerging autonomy (33.8%). Conclusions : Barriers to healthcare reported by young people are multi‐dimensional and have changed over time. Structural barriers, especially cost, are the most prominent among young people. Approaches to overcome structural barriers need to be addressed to better support marginalised young people's healthcare access. Implications for public health : Understanding predictors of different barrier types can inform more targeted approaches to improving access. Equitable access to healthcare is a priority for early diagnosis and treatment in young people, especially reducing out of pocket costs.